Optimised Extension of an Ultra-Low-Power RISC-V Processor to Support Lightweight Neural Network Models - Qiankun Liu; Sam Amiri (Chips, 2025)
With the increasing demand for efficient deep learning models in resource-constrained environments, Binary Neural Networks (BNNs) have emerged as a promising solution due to their ability to significantly reduce computational complexity while maintaining accuracy. Their integration into embedded and edge computing systems is essential for enabling real-time AI applications in areas such as autonomous systems, industrial automation, and intelligent security. Deploying BNN on FPGA using RISC-V, rather than directly deploying the model on FPGA, sacrifices detection speed but, in general, reduces power consumption and on-chip resource usage. The AI-extended RISC-V core is capable of handling tasks beyond BNN inference, providing greater flexibility. This work utilises the lightweight Zero-Riscy core to deploy a BNN on FPGA. Three custom instructions are proposed for convolution, pooling, and fully connected layers, integrating XNOR, POPCOUNT, and threshold operations. This reduces the number of instructions required per task, thereby decreasing the frequency of interactions between Zero-Riscy and the instruction memory. The proposed solution is evaluated on two case studies: MNIST dataset classification and an intrusion detection system (IDS) for in-vehicle networks. The results show that for MNIST inference, the hardware resources required are only 9% of those used by state-of-the-art solutions, though with a slight reduction in speed. For IDS-based inference, power consumption is reduced to just 13% of the original, while resource usage is only 20% of the original. Although some speed is sacrificed, the system still meets real-time monitoring requirements.